2008
DOI: 10.1007/s10545-008-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cirrhosis, dystonia, polycythaemia and hypermanganesaemia—A new metabolic disorder

Abstract: We report a new constellation of clinical features consisting of hypermanganesaemia, liver cirrhosis, an extrapyramidal motor disorder and polycythaemia in a 12 year-old girl born to consanguineous parents. Blood manganese levels were >3000 nmol/L (normal range <320 nmol/L) and MRI revealed signal abnormalities of the basal ganglia consistent with manganese deposition. An older brother with the same phenotype died at 18 years, suggesting a potentially lethal, autosomal recessive disease. This disorder is proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 43 publications
10
136
0
1
Order By: Relevance
“…Several studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernandez et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957) have showed that CaNa2EDTA is clinically effective in the treatment of overt manganism in humans. These observations are consistent with recent therapeutic success in a severe case of genetic hypermanganesemia with extrapyramidal syndrome, polycythemia, and hepatic cirrhosis (Tuschl et al 2008) and possibly in ephedrone-manganic syndrome cases (Selikhova et al 2008). Early studies lacked detailed information on treatment and biomarkers, and other drugs were coadministered, thus potentially confounding the results.…”
Section: Treatmentsupporting
confidence: 78%
See 1 more Smart Citation
“…Several studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernandez et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957) have showed that CaNa2EDTA is clinically effective in the treatment of overt manganism in humans. These observations are consistent with recent therapeutic success in a severe case of genetic hypermanganesemia with extrapyramidal syndrome, polycythemia, and hepatic cirrhosis (Tuschl et al 2008) and possibly in ephedrone-manganic syndrome cases (Selikhova et al 2008). Early studies lacked detailed information on treatment and biomarkers, and other drugs were coadministered, thus potentially confounding the results.…”
Section: Treatmentsupporting
confidence: 78%
“…Manganism is not only an occupational disease, as, even in the absence of relevant exogenous exposures, it can affect patients with chronic liver failure (Hauser et al 1994) (due to impaired biliary excretion of Mn), chronic iron deficiency (Boojar et al 2002;Herrero Hernández et al 2002) mostly due to Fe/Mn competition for transporters (review by Roth & Garrick 2003) (Roth and Garrick 2003), subjects on parenteral nutrition (Fell et al 1996), drug addicts using high Mn injectable solutions (de Bie et al 2007;Levin 2005;Meral et al 2007;Sanotsky et al 2007;Sikk et al 2007), patients in chronic renal failure undergoing hemodialysis (da Silva et al 2007;Ohtake et al 2005) (for unclear reasons), and subjects with genetic defects affecting Mn homeostasis (Tuschl et al 2008). It should be stressed that Fe deficiency affects about 2 billion subjects (Garcia et al 2007) and is a risk factor for Mn neurotoxicity even in absence of relevant exogenous exposures.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…In 2008, Tuschl et al 19 reported a new form of familial parkinsonism in a 12-year old girl with hypermanganesaemia, liver cirrhosis, an extrapyramidal motor disorder and polycythaemia. Her older brother died with the same symptoms.…”
Section: Identification Of Slc30a10mentioning
confidence: 99%
“…Dystonia improved with chelation therapy using calcium EDTA combined with iron supplementation. Although the cause of this syndrome is unknown, an inborn error or manganese metabolism or transport is suggested (Tuschl et al 2008).…”
Section: Metal Storage Disordersmentioning
confidence: 99%